A Novel Photo-labile Caged Peptide for the Repairment of Spinal Cord Injuries - Lu, Chunyu (Université d'Ottawa / University of Ottawa, 2014)
Spinal cord injuries (SCI) are characterized by the inability of mature neurons to regenerate or repair by themselves. In an attempt to overcome the SCI, a novel photo-sensitive cyclic Arg-Gly-Asp-Ser (RGDS) peptide was synthesized using solid phase peptide synthesis (SPSS) to control 3T3 fibroblast cell attachment on hyaluronic acid (HA) hydrogel. The circular RGDS peptide was designed using RGDS sequence labeled with Anp group (3-Na-fmoc-amino-3-(2-nitrophenyl) propionic acid) at the N terminus. The peptide was photo-labile cyclic caged to shelter its bioactivity and UV light was used to make the peptide uncaged. Accuracy of the cyclic caged RGDS peptide was confirmed by high-performance liquid chromatography (HPLC) and mass spectrum (MS). The molecular weight of cyclic caged RGDS peptide was confirmed as 881 by matrix-assisted laser desorption/ionization (MALDI) and electrospray ionization (ESI) mass spectrum. Stability of the cyclic caged RGDS peptide under various pH conditions was verified by circular dichroism spectroscopy. The bioactivity of cyclic caged and uncaged RGDS peptide was tested by photo-controllable directing cell growth based on cell attachment study, cell counting study, and cell morphology study. Three dimensional model structures of cyclic caged and uncaged RGDS peptides were computed by Hyperchem program. The first order reaction theory of Anp uncaging reaction was confirmed by kinetic study. Bioactivity caging and uncaging property of the peptide was also fully confirmed by cell attachment study. This cyclic caged RGDS peptide would be a promising tool in cell patterning for repairing of SCI.
Keywords: Caged Peptide; Cyclic Caging; Photo-labile Peptide